CYBER SECURITY OPERATION AND BASIC EDUCATION MANAGEMENT IN NIGERIA - Amina Akuh, Esther (Antis Publisher, 2025)
Objective: This study investigates the current state of cybersecurity operations and their integration into basic education management in Nigeria, with a focus on identifying benefits, threats, and operational challenges. Method: Employing a qualitative research design, the study conducts a comprehensive review and synthesis of existing literature to examine the interplay between cybersecurity and basic education systems. Results: The findings highlight that integrating cybersecurity into the management of basic education enhances the protection of academic records and personal data of students and staff, while also strengthening institutional integrity. However, the study identifies several challenges, including inadequate funding, limited cyber infrastructure, rapid technological changes, poor personnel training, data management complexities, staff shortages, and risks from third-party and supply chain vulnerabilities. Novelty: This paper contributes to the academic discourse by presenting a contextual analysis of cybersecurity issues within Nigeria’s basic education sector, offering strategic recommendations such as increased funding, infrastructural support, inter-agency collaboration, and targeted capacity-building initiatives to improve cybersecurity integration and resilience in educational institutions.